Antireflection coatings for solar panel power output enhancement. Issue 1771 (21st May 2015) - Pethuraja, Gopal G.; Welser, Roger E.; Zeller, John W.; Puri, Yash R.; Sood, Ashok K.; Efstathiadis, Harry; Haldar, Pradeep; Harvey, Jennifer L.
ABSTRACT: The impact of nanostructured broadband antireflection (AR) coatings on solar panel performance has been projected for a broad range of panel tilt angles at various locations. AR coated films have been integrated on test panels and the short-circuit current has been measured for the entire range of panel tilts. The integration of the AR coatings resulted in an increase in short-circuit current of the panels by eliminating front sheet reflection loss for a broad spectrum of light and wide angle of light incidence. The short-circuit current enhancement is 5% for normal light incidence and approximately 20% for off-angle light incidence. The National Renewable Energy Laboratory (NREL) System Advisor Model (SAM) predicts that this AR coating can yield at least 6.5% improvement in solar panel annual power output. The greatest enhancement, approximately 14%, is predicted for vertical panels. The AR coating's contributions to vertical mount panels and building-integrated solar panels are significant. This nanostructured broadband AR coating thus has the potential to lower the cost per watt of photovoltaic solar energy.